KARAKTER UMBI DAN NUTRISI TUJUH GENOTIP UBI KAYU (Manihot esculenta) - Sri Hartati; Hani Fitriani; Supatmi Supatmi; Enny Sudarmonowati (Universitas Musamus, Merauke, Papua, 2012)
Cassava is one of important sources of carbohydrate and potential to developed as an alternative food diversification. Morfological and nutritional value characterization of cassava’s tuber including β-caroten, protein, Fe and Zn, has been conducted on seven genotypes of cassava. The seven genotypes tested were Adira 1, Adira 4, FEC 25, Mentega 1, Mentega 2, Ubi Kuning and Roti. Tuber of characteristic of seven genotypes showed variation in term of colors of the outer skin, inner tuber’s skin and flesh, root shapes, average tuber weight per plant, length and diameter of the tuber. There was a positive correlation between diamater and weight tuber per plant. Nutritonal content of seven cassava genotypes tested were varied with value ranges 0,011-0,026 ppm, 1,19-2,6%, 34,46-133,07 ppm and 6,63-18,95 ppm for β-caroten, protein, Fe and Zn respectively. The tuber with higer β-caroten content up to 0,011 ppm possessed yellow flesh color. Based on nutritional value data it was found that Mentega 2 containing highest β-caroten, protein, Fe, and Zn.than the others genotypes